2012
DOI: 10.5897/ijwree12.012
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of borehole water quality in Yola-Jimeta Metropolis, Nigeria

Abstract: , pH, sodium (Na + ) and total hardness (CaCO 3 ) are the main sources of borehole water contamination in the study area. This has health implications that include hypertensions and heart and kidney diseases which are on the increase in the region. Poor sanitary condition and intensive use of inorganic fertilizer are implicated as sources of contaminants. We therefore suggest the setting up of water sanitary agencies that will monitor and regulate health based targets of water quality at ward levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
18
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 26 publications
(26 reference statements)
7
18
1
Order By: Relevance
“…Bicarbonate concentration in boreholes in the metropolis ranged from 57.0 mg/L to 399 mg/L, with a mean of 195 mg/L [43]. The present result matches well with the findings of Abubakar et al, [43]. However, HCO 3 -concentration observed in this study disclosed a high level of HCO 3 -in every station compare to the recommended value.…”
Section: Content Of Magnesium (Mgsupporting
confidence: 90%
See 2 more Smart Citations
“…Bicarbonate concentration in boreholes in the metropolis ranged from 57.0 mg/L to 399 mg/L, with a mean of 195 mg/L [43]. The present result matches well with the findings of Abubakar et al, [43]. However, HCO 3 -concentration observed in this study disclosed a high level of HCO 3 -in every station compare to the recommended value.…”
Section: Content Of Magnesium (Mgsupporting
confidence: 90%
“…According to surface water standard, the HCO 3 -concentration in freshwater should be 58.4 mg/L [57]. Bicarbonate concentration in boreholes in the metropolis ranged from 57.0 mg/L to 399 mg/L, with a mean of 195 mg/L [43]. The present result matches well with the findings of Abubakar et al, [43].…”
Section: Content Of Magnesium (Mgsupporting
confidence: 89%
See 1 more Smart Citation
“…This study like similar studies carried out in the North Eastern region of Nigeria, showed that there are incidences of contamination of borehole water. For instance, Abubakar and Adekola (2012) found borehole water from Yola-Jimeta metropolis to have levels of chloride (Cl -), iron (Fe 2+ ), nitrate (NO 3 -), pH, sodium (Na + ) and total hardness (CaCO 3 ) which are the main sources of borehole water contamination in the study area. In that study the upper bound value (US 95 ) of pH was found to be above the guideline value.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that high rainfall is essential in increasing iron concentration in boreholes (Abubakar and Adekola, 2012). Rainwater as it infiltrates the soil and underlying geologic formations dissolves iron, causing it to seep into aquifers that serve as sources of ground water for borehole.…”
Section: Ironmentioning
confidence: 99%